Compound Melody and Jazz Improvisations: A Reconsideration - John D. Check (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
The concept of “compound melody” (a frequent component of Schenkerian analysis) pertains to the way a single line of music projects two or more voice-leading parts. While usually associated with works of the common-practice period, it also plays a role in jazz improvisations. This is especially so in an improvisation by alto saxophonist Paul Desmond, on “All The Things You Are” by Jerome Kern and Oscar Hammerstein II. The voice-leading graphs of this solo, and the attendant commentary, suggest that an awareness and appreciation of compound melody can enable a deeper understanding of jazz styles. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part II).